Centralised and decentralised signal timing optimisation approaches for network traffic control. (April 2020) - Chow, Andy H.F.; Sha, Rui; Li, Shuai
Highlights: Centralised and decentralised algorithms with optimal control formulation. Sensitivity based decentralised signal optimisation algorithms. Comparison with distributed backpressure control policy. Investigation of different network decomposition schemes. Case study of optimisation algorithms on Central London networks. Abstract: This study develops and analyses the centralised and decentralised solution procedures for urban network traffic management through an optimal control framework. The optimal control is formulated based upon the Hamilton-Jacobi formulation of kinematic wave model. Following the problem decomposition under the decentralised scheme, we introduce the use of semi-analytical performance derivatives when developing the decentralised solution algorithm. The proposed control strategies are applied to a set of test scenarios constructed from a real road network in Central London in the UK. Specific interests in the investigation include comparison of the performance gain and computational effort of the two strategies under different circumstances. We also investigate effect of network decomposition strategies on the performance of the solution algorithm. This study generates insight on urban traffic management with use of traffic flow theory, decentralised optimisation, and network decomposition techniques.